Investigação multitemporal de ilhas de calor e de frescor em Maringá, Paraná, utilizando imagens do satélite Landsat 5 - 2000 a 2010 - Germano, Paulo José Moraes Monteiro e Teixeira (2012)
The present study aims to evaluate the occurrence of heat islands and freshness in the city of Maringá / PR, and their relationships with the current urban morphology. The temperatures of zones 1, 2, 5, 10 and 45 were evaluated using satellite images from Landsat 5, which corresponded to the time period 2000 to 2010. With the results presented here, it can demonstrate that the satellite images provided data about the temperatures of the studied areas, which have different temperature values, by having a morphological configuration and distribution of unique urban vegetation. Therefore with data raised in this study, it was concluded that the vegetation roads, the areas with denser vegetation and urban morphology, promoted an effect that managed the distribution and values of temperatures measured for each area .